Proteomic and genomic analyses suggest the association of apolipoprotein C1 with abdominal aortic aneurysm. Issue 10 (19th May 2014) - Moxon, Joseph V.; Liu, Dawei; Moran, Corey S.; Crossman, David J.; Krishna, Smriti M.; Yonglitthipagon, Ponlapat; Emeto, Theophilus I.; Morris, Dylan R.; Padula, Matthew P.; Mulvenna, Jason P.; Rush, Catherine M.; Golledge, Jonathan; et al.
<x xml:space="preserve">Abstract</x> Purpose Abdominal aortic aneurysm (AAA) is an important cause of mortality in the elderly. Mouse models are widely used to investigate AAA pathogenesis but their suitability for biomarker discovery is unexplored. Experimental design We conducted a three‐phase study. Phase 1: Aortas from angiotensin‐II‐infused apolipoprotein E deficient (ApoE−/−) mice with and without AAA were assessed via iTRAQ and analyzed in silico to identify potential circulating markers. Microarray data from ApoE−/− mice and human patients were analyzed in parallel. Phase 2: Putative markers were compared between datasets to shortlist common candidates. Phase 3: The relationship of two shortlisted markers and AAA presence was assessed. Results iTRAQ identified eight proteins with biomarker potential. Microarray data identified 72 and 96 potential biomarkers from ApoE−/− mice and human patients, respectively. All three datasets suggested apolipoprotein C1 (ApoC1) as a marker for AAA; microarray data identified matrix metalloproteinase 9 (MMP9) as a second potential marker. Plasma ApoC1 and MMP9 concentrations positively correlated with AAA diameter in ApoE−/− mice. Conclusions and clinical relevance ApoC1 may be a novel biomarker for AAA.